Differential item functioning of the patient-reported outcomes information system (PROMIS®) pain interference item bank by language (Spanish versus English). - Paz, Sylvia; Spritzer, Karen; Reise, Steven; Hays, Ron; Paz, Sylvia H; Spritzer, Karen L; Reise, Steven P; Hays, Ron D (Quality of Life Research, 2017)
Background: About 70% of Latinos, 5 years old or older, in the United States speak Spanish at home. Measurement equivalence of the PROMIS® pain interference (PI) item bank by language of administration (English versus Spanish) has not been evaluated.Methods: A sample of 527 adult Spanish-speaking Latinos completed the Spanish version of the 41-item PROMIS® pain interference item bank. We evaluate dimensionality, monotonicity and local independence of the Spanish-language items. Then we evaluate differential item functioning (DIF) using ordinal logistic regression with item response theory scores estimated from DIF-free "anchor" items.Results: One of the 41 items in the Spanish version of the PROMIS® PI item bank was identified as having significant uniform DIF.Conclusions: English- and Spanish-speaking subjects with the same level of pain interference responded differently to 1 of the 41 items in the PROMIS® PI item bank. This item was not retained due to proprietary issues. The original English language item parameters can be used when estimating PROMIS® PI scores.